Safety and Regulatory Issues of Nanoencapsulated Food Ingredients - Jafari, Seid Mahdi; Jafari, Seid Mahdi (Academic Press, 2021)
Safety and Regulatory Issues of Nanoencapsulated Food Ingredients, a volume in the Nanoencapsulation in the Food Industry series, discusses the safety and toxicity potential of food-relevant and edible nanostructures, along with legislation issued by different countries and organizations governing their safety. The book's chapters cover safety issues of nanocapsules in food matrices, their possible toxicity effects, and in vitro and in vivo assays which are explored to underline their impact. Authored by a team of global experts in the fields of nano and microencapsulation of food, nutraceutical and pharmaceutical ingredients, this title is of great value to those engaged in fields surrounding nanoencapsulation. - Explores how to analyze the safety of nanoencapsulated bioactive ingredients - Discusses the regulations governing the safety of nanoencapsulated ingredients in different countries - Investigates what agencies and which governmental organizations are responsible for the safety of nanoencapsulated ingredients